2020
DOI: 10.3390/cells9112411
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Pathways Activated by Innate Immunity in Mast Cells: Translating Sensing of Changes into Specific Responses

Abstract: Mast cells (MCs) constitute an essential cell lineage that participates in innate and adaptive immune responses and whose phenotype and function are influenced by tissue-specific conditions. Their mechanisms of activation in type I hypersensitivity reactions have been the subject of multiple studies, but the signaling pathways behind their activation by innate immunity stimuli are not so well described. Here, we review the recent evidence regarding the main molecular elements and signaling pathways connecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 240 publications
2
29
0
Order By: Relevance
“…As components of innate immunity as well as bridges between innate and adaptive immune functions, MCs are ideally localized in tissues to act as sentinels that organize antimicrobial and anti-parasitic defenses [ 74 , 75 ]. On the other hand, MCs can also trigger hypersensitivity reactions upon exposure to exogenous antigens, drugs, venoms, or endogenous alarmins released by damaged or inflamed tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As components of innate immunity as well as bridges between innate and adaptive immune functions, MCs are ideally localized in tissues to act as sentinels that organize antimicrobial and anti-parasitic defenses [ 74 , 75 ]. On the other hand, MCs can also trigger hypersensitivity reactions upon exposure to exogenous antigens, drugs, venoms, or endogenous alarmins released by damaged or inflamed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In response to ligand binding, the ST2/IL-1RacP complex will initiate a sequence of phosphorylation and ubiquitination events starting with the recruitment of the adapter MyD88 (myeloid differentiation primary response gene 88) through its TIR domain (toll/interleukin-1 receptor), followed by members of the IRAK family (interleukin-1 receptor–associated kinase), the E3 ubiquitin ligase TRAF6 (TNF receptor-associated factor 6), and eventually TAK1 (TGF-β-activated kinase 1) [ 68 , 74 , 82 , 83 ]. TAK1 is the starting point of several cascades, among which are the stress-associated kinases p38 and JNK as well as NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Agonists encompass not only multiple cationic drugs, but also antimicrobial and neuropeptides like Substance P (SP), making it a universally operating receptor of MCTC-type MCs [ 4 , 6 ]. MRGPRX2’s importance as a central signaling unit of this MC type has been widely recognized by the MC community [ 10 , 11 , 12 , 13 , 16 , 65 , 66 , 67 ]. As research into MRGPRX2 began only recently, less is known about its modulation by autocrine and paracrine factors compared to FcεRI.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are able to recognize many different PAMPs, mainly through the use of cell surface pattern recognition receptors (PRRS) such as TLRs [ 20 , 21 ]. What TLRs are actually expressed on mature mast cells is currently a matter of debate, with different studies showing conflicting results [ 41 ]. Surprisingly, a proteome study on human and mouse primary mast cells found an absence of many innate immune sensors, including all TLRs [ 42 ].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Despite this, TLR agonists can cause changes in gene expression, release of inflammatory mediators and mast cell migration in several models [ 43 ]. While some studies show otherwise, TLR activation is generally not thought to lead to rapid degranulation as seen with activation of FcεRI [ 41 , 43 ]. Mast cells can also utilize Dectin-1 to sense β-glucans from fungi [ 44 ] and the intracellular receptors RIG-I, MDA5 and TLR3 to detect viruses [ 45 , 46 , 47 ].…”
Section: Innate Immunitymentioning
confidence: 99%